Influence of nine week balance training program on one leg stand performance - Roos, L.; Maeder, U.; Wyss, T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Balance is crucial in everyday activities such as walking or climbing stairs. In military basic training balance is even more important since recruits have to perform a large number of physical activities on uneven surfaces often while carrying heavy loads. Research suggests that a specific training can improve balance performance[1]. Therefore, the objective of this study was to investigate the improvement of the balance ability over a 9 week training program. Methods: In this study 406 male recruits of the infantry training camp in Aarau, Switzerland volunteered during their basic training. Thereof, 243 recruits were chosen to participate in a 9 week balance training program. A 30 minutes program was included into the army sports training of 180 minutes per week. The 163 recruits of the control group participated in the normal army sports training comprised of endurance runs, strength and coordination training and sports. To test the recruits` balance abilities a one leg stand [2] was performed in week 1 and week 11 of basic training. Results: Control and intervention group showed a significant increase of the one leg stand duration over the 11 weeks of basic training, 9.06 +/- 13.46 s and 12.71 +/- 15.40 s respectively. However, the difference in performance enhancement between the groups was significant (p=0.014). There was no significant difference in total duration of sport (140.21 +/- 76.96 vs. 145.24 +/- 27.80 minutes per week), amount of trainings per week (1.73 +/- 0.63 vs. 1.86 +/- 0.35) or self reported intensity (2.26 +/- 0.23 vs. 2.35 +/- 0.39 on a scale of 1 to 3) between control and intervention group. Discussion Both groups increased the total duration of one leg stand suggesting that the activities executed during daily military training already increase the recruits` balance abilities to a certain degree. The most common military actions such as lifting, carrying loads while marching, climbing, crawling, jumping, digging [3] require good balance and core strength to succeed. However, the intervention group had a significantly higher performance increase. A balance training as deployed here, therefore, could be useful for injury prevention during military basic training [1].